Improving the Nutrient Quality of Juice Wastes Mixture Through Fermentation by Using Trichodherma viride for Poultry Diet - Rizal, Yose; Mahata, Maria Endo; Joli, Indra; Wu, Guoyao (Pakistan Journal of Nutrition, 2012)
Two experiments were conducted to improve Juice Wastes Mixture’s (JWM’s) nutrient quality by using Trichoderma viride and to compare between treated vs. untreated one. This JWM consists of carrot, apple, mango, avocado, orange, melon and tree-tomato in the same proportion. Experiment 1 was performed in a 3 x 5 factorial experiment of completely randomized design with 3 replicates. First factor was Trichoderma viride concentration (5, 7 and 9%) and second factor was incubation period (0, 5, 7, 9 and 11 days). Measured variables were Crude Fiber (CF), Crude Protein (CP) and Ether Extract (EE). Experiment 2 was to compare nutrient content between treated vs. untreated one. Measured variables were JWM’s CF, CP, EE, NDF, ADF, cellulose, hemi-cellulose, lignin, nitrogen retention, amino acid profile and Metabolizable Energy (ME). There was a very significant (p